A Chlamydomonas-derived Human Papillomavirus 16 E7 vaccine induces specific tumor protection. - Olivia C Demurtas (Public Library of Science (PLoS), 2013)
Background The E7 protein of the Human Papillomavirus (HPV) type 16, being involved in malignant cellular transformation, represents a key antigen for developing therapeutic vaccines against HPV-related lesions and cancers. Recombinant production of this vaccine antigen in an active form and in compliance with good manufacturing practices (GMP) plays a crucial role for developing effective vaccines. E7-based therapeutic vaccines produced in plants have been shown to be active in tumor regression and protection in pre-clinical models. However, some drawbacks of in whole-plant vaccine production encouraged us to explore the production of the E7-based therapeutic vaccine in Chlamydomonas reinhardtii, an organism easy to grow and transform and fully amenable to GMP guidelines. Methodology/principal findings An expression cassette encoding E7GGG, a mutated, attenuated form of the E7 oncoprotein, alone or as a fusion with affinity tags (His6 or FLAG), under the control of the C. reinhardtii chloroplast psbD 5' UTR and the psbA 3' UTR, was introduced into the C. reinhardtii chloroplast genome by homologous recombination. The protein was mostly soluble and reached 0.12% of total soluble proteins. Affinity purification was optimized and performed for both tagged forms. Induction of specific anti-E7 IgGs and E7-specific T-cell proliferation were detected in C57BL/6 mice vaccinated with total Chlamydomonas extract and with affinity-purified protein. High levels of tumor protection were achieved after challenge with a tumor cell line expressing the E7 protein. Conclusions The C. reinhardtii chloroplast is a suitable expression system for the production of the E7GGG protein, in a soluble, immunogenic form. The production in contained and sterile conditions highlights the potential of microalgae as alternative platforms for the production of vaccines for human uses.